Perception of visitors towards the role of zoos: a Malaysian perspective - Puan, Chong Leong; Hussin, Mohamed Zakaria (Wiley Interscience, 2007)
Zoos have multiple roles in recreation, conservation, education and research. There is a lack of information on the motivation and expectation of local visitors who visit zoos in developing countries. A social survey was carried out to identify the perception of visitors towards the roles of three Malaysian zoos. The results indicate that visitors who go to the zoo mainly do so for recreation and they prefer to see attractive and active animals, rather than threatened and healthy animals, although the variation in the mean scores of these perceptions was minimal. The majority of respondents perceived that animals were kept mainly to attract visitors. However, most respondents were knowledgeable on issues related to conservation, education and research in zoos, and would like to see zoos move towards achieving these goals. The respondents perceived the zoos, in priority order, as places for conservation, education, research and recreation. These results may provide some guidance for local zoos in future planning, in particular in designing and improving the facilities and exhibits in order to fulfil their roles effectively.